1987
DOI: 10.1080/15298668791384689
|View full text |Cite
|
Sign up to set email alerts
|

A Demonstration of NIOSH Push-Pull Ventilation Criteria

Abstract: This paper summarizes the results of a study performed on an actual chrome plating tank in order to validate criteria for push-pull ventilation systems developed by Huebener and Hughes at NIOSH. Validation of the criteria was made by taking area industrial hygiene samples for hexavalent and total chrome at ten locations around the plating tank. The sampling was performed during actual production runs or while the tank was operating with a dummy load. The sampling data are summarized. The data show that the pus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…During the 1980s, the United States' National Institute for Occupational Safety and Health (NIOSH) published a series of papers giving the results of experimental work. Two papers, Hughes and Huebener (1982) and Huebener and Hughes (1985), reported the results of experimental work on the push-pull system in laboratory conditions, and suggested minimum flow rates for the inlet (per unit width of tank) and outlet (per unit surface area of tank) for different sizes of tank in the range 1.2 x 1.2-1.2 x 1.8 m. Klein (1985Klein ( , 1987 published the results of further work by NIOSH which used the laboratory data of Huebener and Hughes (1985) in an industrial situation, and the results showed that Huebener and Hughes' data were valid in practical situations, even with significant obstructions in the path of the jet. Heinsohn (1991) used the computational algorithm SIMPLER, a method devised by Patankar (1980), to solve the flow in the two-dimensional push-pull system and gave recommendations for the jet and exhaust flow rates.…”
Section: Review Of Previous Work On the Push-pull Systemmentioning
confidence: 99%
“…During the 1980s, the United States' National Institute for Occupational Safety and Health (NIOSH) published a series of papers giving the results of experimental work. Two papers, Hughes and Huebener (1982) and Huebener and Hughes (1985), reported the results of experimental work on the push-pull system in laboratory conditions, and suggested minimum flow rates for the inlet (per unit width of tank) and outlet (per unit surface area of tank) for different sizes of tank in the range 1.2 x 1.2-1.2 x 1.8 m. Klein (1985Klein ( , 1987 published the results of further work by NIOSH which used the laboratory data of Huebener and Hughes (1985) in an industrial situation, and the results showed that Huebener and Hughes' data were valid in practical situations, even with significant obstructions in the path of the jet. Heinsohn (1991) used the computational algorithm SIMPLER, a method devised by Patankar (1980), to solve the flow in the two-dimensional push-pull system and gave recommendations for the jet and exhaust flow rates.…”
Section: Review Of Previous Work On the Push-pull Systemmentioning
confidence: 99%
“…3–5 In 1982 and 1985, Huebner and Hughes 6,7 provided some empirical values for supply air velocity and suction velocity for different surface treatment tanks using theoretical analysis and experiments. Klein 8 and Matthew 9 applied Huebner and Hughes’s achievements to practical industries and corrected the supply air velocities and suction velocities for some special conditions. Since the 1990s, the airflow characteristics of surface treatment tanks with push–pull ventilation systems 10,11 have received attention from studies of computational fluid dynamics (CFD).…”
Section: Introductionmentioning
confidence: 99%
“…(4,5) Design guidelines for push-pull ventilation systems are based mainly on experimental data, especially those summarized in the series of articles published in the 1980s by the United States National Institute of Occupational Safety and Health. (3,6,7) They give recommendations for a restricted range of operating and environmental parameters. (2,8) Although useful, these guidelines do not allow for predicting either the concentration of pollutant close to the open tank or the influence of several important operating parameters, such as airflow rates (both blowing and exhaust), geometry of the tank, and room air currents.…”
mentioning
confidence: 99%